Thermal effects in rainbow trout (Oncorhynchus mykiss) F1 embryos (farmed female × wild thermal-resistant male) - Crichigno, Sonia Alejandra (2021)
The aim of this work was to investigate the response of rainbow trout embryos (Oncorhynchus mykiss) (i.e., survival, size at hatching, time to hatching, malformations) to four incubation temperatures (5.8, 8.9, 14.0 and 16.8 C), taking into account the origin of the male parental genome and comparing pure farmed and F1 embryos (farmed female × wild thermal-resistant male). Several consequences of thermal stress were observed: lower accumulated thermal units (ATU) at hatching at high temperatures, and lower survival, shorter hatched free embryos and less-consumed yolk sac at extreme temperatures. The effect of the thermal-adapted male parental genome was shown only in the lower percentage of incompletely hatched free embryos in the F1 families. It appears that to obtain greater modification of thermal performance during early development, the adapted genome of the wild thermalresistant population has to be included through maternal inheritance, thus producing a stabilized strain selected for domesticity, growth and thermal adaptation.